Effectiveness of kinesio taping on postoperative morbidity after impacted mandibular third molar surgery: a prospective, randomized, placebo-controlled clinical study - Ufuk TATLI; Ilke Coskun BENLIDAYI; Fariz SALIMOV; Rengin GUZEL (University of São Paulo, 2020)
Abstract Objective Our study seeks to investigate the effectiveness of kinesio taping (KT) on postoperative morbidity compared to placebo and control groups after impacted third molar surgery. Methodology Sixty patients with impacted mandibular third molar were included in this prospective, randomized, placebo-controlled clinical study. After surgical extraction of the impacted tooth, patients were allocated into three groups (20 patients each): group 1 received KT (kinesio), group 2 received placebo taping (placebo), and group 3 received no taping (control). The groups were compared regarding facial swelling, pain and trismus. Swelling was evaluated using a tape measuring method. Pain was assessed by a visual analog scale and the number of analgesic tablets taken. Trismus was determined by measuring maximum mouth opening. Results In the KT group, all parameters reduced significantly on 2nd and 4th postoperative days compared to other groups; however, placebo and control groups revealed comparable outcomes. On 7th day, all groups showed comparable results. Conclusions The KT application is an effective method for reducing morbidity after impacted mandibular third molar surgery. However, placebo taping is not as effective as proper taping. Placebo taping shows similar results compared to no taping regarding facial swelling percentage, pain and trismus.